Radiation Dose Reduction: Comparing The Amount Of Publications Published In Diagnostic And Interventional Radiology (Journal of Namibian Studies : History Politics Culture, 2017)
Our goal was to compare and measure the level of awareness among the diagnostic and interventional radiology communities about radiation dose reduction.Methods: Between 2005 and 2015, the search terms "interventional/computed tomography" and "radiation dose/radiation dose reduction" were used to analyze abstracts accepted to the annual meetings of the Society of Interventional Radiology (SIR), the Cardiovascular and Interventional Radiological Society of Europe (CIRSE), the Radiological Society of North America (RSNA), and the European Congress of Radiology (ECR). The aforementioned search terms were used in a PubMed query covering the years 2005–2015.In conclusion, there may be a need for more education and discussion on this subject given that the rise in abstracts about radiation dose reduction that has been observed in the field of interventional radiology over the past ten years has not coincided with the increase in volume observed in diagnostic radiology.